Serum Interleukine 35 in Iraqi female patients with newly diagnosed of rheumatoid arthritis. - Anwar F. Al-Tai (مجلة كلية الطب, 2014)
Background: Rheumatoid arthritis (RA) characterized by local and systemic effects of inflammation has a wide range of biochemical markers implicated directly or indirectly to its pathogenesis.